Severe acute malnutrition's recovery rate still below the minimum standard: predictors of time to recovery among 6- to 59-month-old children in the healthcare setting of Southwest Ethiopia - Seyum Ebissa Eyi; Gebiso Roba Debele; Efrem Negash; Kebebe Bidira; Debela Tarecha; Kabtamu Nigussie; Mohammedamin Hajure; Mohammedjud Hassen Ahmed; Bilisumamulifna Tefera Kefeni (BMC, 2022)
Abstract Background Despite currently available, scientifically proven treatments and national guideline, the SAM recovery rate is still considerably behind expectations, and it continues to have a devastating impact on under-five children. Identifying predictors of time to recovery might help to reach the minimal criterion established by the WHO and the national Sphere which decreases child mortality. Therefore, the current study assessed time to recovery and its predictors among children aged 6-59 months admitted with SAM in the Healthcare Setting of Southwest Ethiopia, 2021. Methods An institutional-based multicenter retrospective follow-up study was conducted on 486 children aged 6 to 59 months admitted with SAM cases. Data were entered into Epi-Data version 4.6 and exported to Stata version 14 for further analysis. Cox-Snell residual plot was used to assess the final model's overall goodness of fit. Finally, a significant predictor of time to recovery was identified using Weibull survival regression model, at 0.05 significance level. Result Overall, 68.72 (95% CI 64.8, 73) of the children recovered and 4.32% died. The overall incidence density was 3.35/100-person day. Independent predictors of time to recovery were, starting complementary feeding at six months (AHR = 1.44; 95%, CI 1.073, 1.935), pneumonia at baseline (AHR = 1.33, 95%, CI 1.049, 1.696), amoxicillin (AHR = 1.31, 95%, CI 1.021, 1.685), and folic acid supplementation (AHR = 1.82, 95% CI 1,237, 2.665). Conclusion The recovery from SAM at study area after a maximum of 60 days of treatment was below the accepted minimum standard. Complementary feeding, pneumonia, treated by amoxicillin, and folic acid supplementation were predictors of time to recovery. Therefore, providing folic acid and amoxicillin for those in need as well as the earliest possible treatment of concomitant conditions like pneumonia is highly recommended.